Key-dependent s-box in lightweight block ciphers - AlDabbagh, S.S.M.; Taha Alshaikhli, Imad Fakhri; Zaba, Muhammad Reza (Little Lion Scientific Islamabad Pakistan, 2014)
This paper introduces new methods of how to generate a suitable key-dependent substitution boxes (Sboxes) for use in lightweight block ciphers. An S-box is commonly used in block ciphers to provide the crucial property of nonlinearity. And one of the advantages of using key-dependent S-boxes is that it is difficult for an attacker to perform attacks such as differential cryptanalysis on the cipher since the S-boxes are unknown. However, implementing such S-box incurs costs, which is one of the criteria that a lightweight block cipher has to minimize. It is therefore important to have a key-dependent S-box method which always outputs a cryptographically strong S-box and has a small footprint. In this paper, we propose novel methods on how to generate s-boxes based on the value of the secret key. Moreover, this research showed the intensive analysis for cost and security for each method.